Ultrasonic Study of Binary Mixture of N-Butyl Alcohol and Aniline at Room Temperature (International Journal of Scientific Research in Science and Technology, 2024)
Density (r) and viscosity (h) have been calculated for n-Butyl Alcohol, Aniline and their binary mixtures at room temperature. Ultrasonic Velocity (U) have been measured for pure liquids and their binary mixtures using Ultrasonic interferometer at 2MHz frequency. Experimental data have been used to calculate some derived parameters such as adiabatic compressibility (b), acoustical impedance (Z), relaxation time (t), free length () and free volume (). Also the excess parameters such as excess ultrasonic velocity DU, excess acoustical impedance (DZ), excess relaxation (Dt), excess free length (D) and excess free volume (D These parameters have been evaluated and discussed in light of intermolecular interaction in these mixtures.